Dataset for Investigating the effects of rearing conditions and generation divergence on cuticular hydrocarbon profiles of Lucilia sericata adult flies - Moore, Hannah (Cranfield University, 2024)
Blowflies (Diptera: Calliphoridae) are known to be the most forensically important insects in forensic entomology as they are the first insects to arrive at decomposing remains, thus they have been used for decades to estimate the minimum post-mortem interval (PMImin). Accurate estimations of PMImin are essential for effective forensic investigations. However, challenges arise when multiple generations of adult flies are associated with decomposing remains, leading to lapses in PMImin predictions. To address this issue, the present study focuses on analysing cuticular hydrocarbons (CHCs) as a novel approach to identify insect species, estimating their age and determining the environment in which they develop. Previous studies have explored CHC analysis and contributed to the validation of the technique; nevertheless, generation differences and long-term rearing effects remain undetermined, especially their direct influence on CHC profiles. Therefore, this investigation examines the chemical profiles of first-generation strains reared in both outdoor and indoor settings to examine the impact of rearing conditions on Lucilia sericata adult flies. Furthermore, a comparative analysis between first- and fourth-generation adult flies is conducted to evaluate the long-term rearing effects in laboratory conditions and to explore intergeneration differences between the strains. The profiles were analysed by gas chromatography–mass spectrometry (GC–MS). Samples were classified with a multivariate statistical method, principal component analysis (PCA) to visualise distinctions in the chemical profiles. The study contributes to the existing literature by revealing the profound influence of generation divergence and environmental conditions on CHC profiles. The comprehensive analysis presented in this study serves to enhance the understanding and application of CHC analysis in forensic entomology, ultimately advancing the reliability and precision of forensic investigations involving decomposing remains.
Keywords: 'Calliphoridaeblowflies; forensic entomology; cuticular hydrocarbons; Lucilia sericata; rearing conditions; generation differences; Gas Chromatography-Mass Spectrometry; Principal Component Analysis'